Nilai-Nilai Sufistik dalam Proses Bimbingan Perkawinan - Hakiki, Nurul (Jurnal Riset Agama, 2022)
Conflicts in the household occur because of the lack of education of the bride and groom and lack of understanding and knowledge about domestic life. Sufistic values are a way to resolve conflicts in the household. This study aims to find out what Sufistic values are. Second, knowing how the marriage guidance process is at the Office of Religious Affairs in Cidahu District. Third, to find out how Sufistic values are in the marriage guidance process at the Office of Religious Affairs, Cidahu District. The research method used is a qualitative method in which the data source comes from the results of observations and interviews as well as other literature related to the research theme. The results of this study indicate that Sufistic values are attributes that are aimed only at God, their obedience cannot be shaken by anything so that events in the world will not affect them. The marriage guidance process at the Cidahu District Religious Affairs Office has been going well, the extension workers follow the existing regulations, and the participants are enthusiastic in the marriage guidance process. Sufistic values in the marriage guidance process are patience, gratitude, reflection, sincerity, pleasure, and trust.